Tecnologias digitais, ensino remoto emergencial e prática pedagógica de biologia no ensino médio: reflexões sobre o fazer do professor - Silva, Ana Karine Ribeiro da Silva (2023)
The research deals with the use of Digital Technologies (DT) in the work with the Biology subject component, during the Emergency Remote Teaching (ERE) period. The general objective is to understand how the pedagogical practices, mediated by Digital Technologies, were carried out in the teaching of Biology, during the synchronous activities at the ERE, from March to July 2021. The problem stems from the following research question: how do Biology of the Assis Chateaubriand Integrated Education Center carried out DT-mediated pedagogical practices during synchronous classes at ERE? The research, of a qualitative and participatory nature, provided an opportunity to discuss the contributions of didactic-pedagogical mediation, carried out in an online virtual platform, as possibilities for teaching, beyond the physical school space. In order to carry out the research, due to the structural nature of the methodology, the netnographic method was chosen, using the online questionnaire, available to participants through Google Forms, and the Discussion Group as devices for the construction of information. As a locus, there is the Assis Chateaubriand Integrated Education Center, in Feira de Santana, with the participants initially being four teachers of the Biology subject component, who work in High School, noting that four answered the questionnaire and three participated in the group of discussion. The research revealed contributions and challenges provided by the use of DT in synchronous class contexts, which reverberate in the elaboration of the pedagogical planning and in the selection of digital interfaces for the class during the ERE. It also provided the opportunity to create a reflective space on the teacher's work during the pandemic period, as a way to stimulate questioning about the role of DT in teaching.